2009
DOI: 10.1007/s10330-009-0157-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological significance and relations of Caspase-3 expression, cell proliferation and apoptosis in gastric cancer and the precancerous lesions

Abstract: Objective: We investigated the relationship between the expression of Caspase-3, cell proliferation and apoptosis in gastric cancer and their precancerous lesions, to explore the tumorigenesis of the stomach mucosa. Methods: Caspase-3 expression in 13 normal gastric mucosa, 6 chronic atrophic gastritis (CAG), 31 intestinal metaplasia (IM), 114 dysplasia (DYS) and 20 gastric carcinomas were investigated immunohistochemically. Cell proliferation was evaluated with anti-Ki-67 immunostaining and apoptosis was eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…This difference is perhaps due to the fact that present study focuses the analysis of chemical coding of neurons in the MPs but not expression of these enzymes inside gastric cancer tissue. It should be also underline that Hu et al [ 23 ] observed that CASP3 expression was up-regulated in chronic atrophic gastritis, intestinal metaplasia and mild-moderate atypical dysplasia, while tissues with severe dysplasia presented down-regulation of this endoprotease. Moreover, this low expression of CASP3 signified an ominous prognosis in gastric cancer [ 24 ].…”
Section: Discussionmentioning
confidence: 96%
“…This difference is perhaps due to the fact that present study focuses the analysis of chemical coding of neurons in the MPs but not expression of these enzymes inside gastric cancer tissue. It should be also underline that Hu et al [ 23 ] observed that CASP3 expression was up-regulated in chronic atrophic gastritis, intestinal metaplasia and mild-moderate atypical dysplasia, while tissues with severe dysplasia presented down-regulation of this endoprotease. Moreover, this low expression of CASP3 signified an ominous prognosis in gastric cancer [ 24 ].…”
Section: Discussionmentioning
confidence: 96%